Community Health Risk Awareness and Knowledge of Air Pollution in Annadale, Polokwane Local Municipality, Limpopo Province, South Africa - Famola Charles Ngobeni; Mokoko Percy Kekana (SAGE Publishing, 2024)
Background: Exposure to air pollution has detrimental effects on the elderly, women, people with pre-existing medical conditions, people living in poverty and children. The aim of the study was to investigate the extent of community awareness and knowledge on the health risks associated with exposure to air pollution. The study was conducted at Annadale residential area locally known as Ladanna surrounded by industrial areas and located in Polokwane Local Municipality under Capricorn District Municipality in Limpopo Province, South Africa. Methods: A cross-sectional study design was used for the study, using self-administered questionnaires. The questionnaire was pre-tested on 10 respondents at Emdo Park (Extension 29) in Polokwane from 02 to 06 February 2021 and another fifteen respondents were pre-tested at Lesedi Park. A simple random sampling technique was used to select 376 respondents. Systematic sampling method was applied to select the households. SPSS version 26 was used to analyze data. Data was presented in the form of frequencies and percentages. Spearman rank correlation was used to measure the degree of association between 2 variables. A Chi-square test was used to compare the groups between the categorical variables. Multivariate Logistic Regression Model was used to assess associations of knowledge/awareness outcomes and sociodemographic characteristics with odds ratios (ORs) and 95% confidence intervals (Cls) presented. Results: Of 376 respondents, 221 (59%) were males and 154 (41%) females. The majority 113 (70%) of respondents were those between the age group 23 and 47 years and 353 (94%) were aware that if they don't protect themselves against polluted air, they may get sick, with age and educational status associated with their awareness ( P  < .05). About 361 (96%) knew what air pollution is and 188 (50%) think the air they breathe in Annadale is moderate. A total number of 278 (74%) said they feel sick/uncomfortable when the quality of air is bad. About 293 (78%) knew that people are exposed to air pollution by breathing contaminated air and 237 (63%) identified sewage smell as the main cause of air pollution. Internet 199 (53%) and television 177 (47%) were identified as the main source of information Those who were not aware of actions implemented to reduce air pollution were 180 (48%). Based on the results of the study, respondents' level of knowledge in Annadale was poor (71%) and their awareness was good (87%). Conclusions: It is crucial that air pollution risk communication strategies be implemented to empower residents and improve the level of knowledge on the dangers of exposure to polluted air.